Identification of host proteins interacting with the E protein of porcine epidemic diarrhea virus - Qiu, Yingwu; Sun, Yingshuo; Zheng, Xiaoyu; Gong, Lang; Yang, Liangyu; Xiang, Bin (Frontiers in Microbiology, 2024)
Introduction: Porcine epidemic diarrhea (PED) is an acute, highly contagious, and high-mortality enterophilic infectious disease caused by the porcine epidemic diarrhea virus (PEDV). PEDV is globally endemic and causes substantial economic losses in the swine industry. The PEDV E protein is the smallest structural protein with high expression levels that interacts with the M protein and participates in virus assembly. However, how the host proteins interact with E proteins in PEDV replication remains unknown. Methods: We identified host proteins that interact with the PEDV E proteins using a combination of PEDV E protein-labeled antibody co-immunoprecipitation and tandem liquid-chromatography mass-spectroscopy (LC-MS/MS). Results: Bioinformatical analysis showed that in eukaryotes, ribosome biogenesis, RNA transport, and amino acid biosynthesis represent the three main pathways that are associated with the E protein. The interaction between the E protein and isocitrate dehydrogenase [NAD] β-subunit (NAD-IDH-β), DNA-directed RNA polymerase II subunit RPB9, and mRNA-associated protein MRNP 41 was validated using coimmunoprecipitation and confocal assays. NAD-IDH-β overexpression significantly inhibited viral replication. Discussion: The antiviral effect of NAD-IDH-β suggesting that the E protein may regulate host metabolism by interacting with NAD-IDH-β, thereby reducing the available energy for viral replication. Elucidating the interaction between the PEDV E protein and host proteins may clarify its role in viral replication. These results provide a theoretical basis for the study of PEDV infection mechanism and antiviral targets.